2022
DOI: 10.3390/biom12050667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Palmitoylethanolamide on Neurodegenerative Diseases: A Review from Rodents to Humans

Abstract: Palmitoylethanolamide (PEA) stands out among endogenous lipid mediators for its neuroprotective, anti-inflammatory, and analgesic functions. PEA belonging to the N-acetylanolamine class of phospholipids was first isolated from soy lecithin, egg yolk, and peanut flour. It is currently used for the treatment of different types of neuropathic pain, such as fibromyalgia, osteoarthritis, carpal tunnel syndrome, and many other conditions. The properties of PEA, especially of its micronized or ultra-micronized forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…The decreased ROS also improves mitochondrial function, ameliorating the brain environment and facilitating the recovery of neuronal connections [ 30 ]. In preclinical studies of neuroinflammatory disorders, co-ultra-micronized PEA and luteolin improve neuroprotection compared with either molecule alone [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased ROS also improves mitochondrial function, ameliorating the brain environment and facilitating the recovery of neuronal connections [ 30 ]. In preclinical studies of neuroinflammatory disorders, co-ultra-micronized PEA and luteolin improve neuroprotection compared with either molecule alone [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation is a localized inflammation occurring in the PNS and CNS in response to trauma, bacterial/viral infection, autoimmunity, and/or toxins [ 83 , 84 ]. In particular, neuroinflammation is a common feature across different conditions, including neurodegenerative diseases, fibromyalgia, and chronic pain [ 83 , 85 , 86 ]. Different studies have reported the effect of PEA in the management of pain and inflammatory conditions [ 87 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first systematic review of all studies investigating the biobehavioral effects of palmitoylethanolamide (PEA) with reference to cognitive decline, that is the core symptomatologic domain of neurocognitive disorders (NCDs) ( 4 ). Independently of potential effects of PEA on additional features of NCDs, such as motor impairments, pain, and overall disability [recently reviewed here ( 57 )], disentangling whether PEA is effective in improving cognition, possibly corroborated by evidence of a restoring effect on its neurobiological underpinnings, is of paramount importance to tip the scales toward considering PEA an adjunctive therapeutic option for NCDs. Based on evidence that degeneration of basal forebrain neurons causes a loss of cholinergic tone in the basal forebrain cholinergic system, with implications for the development of cognitive decline ( 58 ), most research has focused on the role of acetylcholinesterase (AChE) inhibitors as a potential treatment for NCDs ( 59 ).…”
Section: Discussionmentioning
confidence: 99%